A First in Human Trial Implanting Microalgae Shows Safety of Photosynthetic Therapy for the Effective Treatment of Full Thickness Skin Wounds - Obaíd, Miguel Luis; Camacho, Juan Pablo; Brenet, Marianne; Corrales-Orovio, Rocío; Carvajal, Felipe; Martorell, Ximena; Werner, Consuelo; Simón, Valeska; Varas, Juan; Calderón, Wilfredo; Guzmán, Christian Dani; Bono, María Rosa; et al. (Frontiers in Medicine, 2021)
Insufficient oxygen supply represents a relevant issue in several fields of human physiology and medicine. It has been suggested that the implantation of photosynthetic cells can provide oxygen to tissues in the absence of a vascular supply. This approach has been demonstrated to be successful in several in vitro and in vivo models; however, no data is available about their safety in human patients. Here, an early phase-1 clinical trial (ClinicalTrials.gov identifier: NCT03960164, https://clinicaltrials.gov/ct2/show/NCT03960164) is presented to evaluate the safety and feasibility of implanting photosynthetic scaffolds for dermal regeneration in eight patients with full-thickness skin wounds. Overall, this trial shows that the presence of the photosynthetic microalgae Chlamydomonas reinhardtii in the implanted scaffolds did not trigger any deleterious local or systemic immune responses in a 90 days follow-up, allowing full tissue regeneration in humans. The results presented here represent the first attempt to treat patients with photosynthetic cells, supporting the translation of photosynthetic therapies into clinics. Clinical Trial Registration:www.clinicaltrials.gov/ct2/show/NCT03960164, identifier: NCT03960164.